«Quel misterioso fondo del nostro essere»: una glossa a Die Geburt der Tragödie, di Nietzsche - Giancarla Sola (Firenze University Press, 2013)
The article is focused on Nietzsche's work entitled Die Geburt der Trägodie and his aim is to interpret the relationship between the problem of "Ursprüngli- chkeit" and the concept of "Bildung". In other words, the attention is directed at the formation of the human being and his original dimension.More specificly, the pedagogical analyse is concentrated on the attack that Nietzsche addresses to the modern individual, which nowadays is only the appear- ance of himself.